A Novel Thickening Agent Made from a Mixture of Cassava and Corn Flour for the Production of Edible Mushroom Growing Media - Alfred Apaab Kiame; Timothée Mananga Nkodi; Jean Paul Koto-Te-Nyiwa Ngbolua; Alain Nkongolo Tshisuaka; Nicolas Kalulu Taba; Joseph Kasali Lumande; Simon Mpulusu Dibaluka (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2026)
According to the FAO, sub-Saharan Africa population’s diet has a real deficit in animal protein for several reasons, including low animal production, rapid population growth, economic factors, etc. To compensate for this deficiency, the population turn to consuming mushrooms harvested seasonally, which are unfortunately becoming scarce due to deforestation. This has led to a shift towards mushroom cultivation, which necessarily requires the use of agar as a reference solidifying agent for the culture medium. However, agar is an imported product that is not accessible to all social classes. Hence, the aim of this research was to compare agar with three other solidifying agents: A1, A2, and A3, composed respectively of 1:1; 1:2, and 2:1 (cassava flour:corn flour, pretreated in an oven at 157.5 ±3.54 °C). When preparing the culture media with these three solidifiers, the best gel was obtained from solidifying agent A3, with which the fungal species Pleurotus oestratus was inoculated. On the third day, the mycelia had invaded all nine tubes of the agar medium, almost reaching the mother culture at the same time (three days) as the reference medium prepared with agar as the solidifying agent (PDA). To ensure the viability of our culture medium prepared with A3, the seed stock and seed led to the production of sporophores, proving that solidifying agent A3 can effectively replace agar, especially in developing countries.